A functionalized dumbbell probe-based cascading exponential amplification DNA machine enables amplified probing of microRNAs. Issue 11 (15th January 2020) - Wang, Jie; Li, Shuhui; Xu, Jianguo; Lu, Yusheng; Lin, Min; Wang, Chaihung; Zhang, Chen; Lin, Guoxing; Jia, Lee
Abstract : A functionalized dumbbell probe-based cascading exponential amplification DNA machine has been developed for robust determination of miRNA-21. Abstract : A functionalized dumbbell probe (FDP) based amplification method, termed as a cascading exponential amplification DNA machine (CEA-DNA machine), has been developed to autonomously accumulate single G-quadruplexes (SGQs) and twin-G-quadruplexes (TGQs) for robust fluorescence signal-on probing of miRNA-21.